2004
DOI: 10.1007/s00414-004-0511-y
|View full text |Cite
|
Sign up to set email alerts
|

Commotio cordis?A report of three cases

Abstract: Commotio cordis is a recognised cause of sudden death in which an apparently minor blow to the chest causes ventricular fibrillation and cardiac arrest. It is best known for causing death during games of youth baseball in the United States, but individual cases have been recorded as a result of a wide range of activities, principally sporting. The underlying biochemical and mechano-electric causes have been well documented. However, there are few reported cases where commotio cordis is implicated as the cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Ischemia is the most likely culprit for this inhomogeneity, but the findings of focal myocardial necrosis and/or fibrosis are common in cases of sudden arrhythmic death and are often assumed to be the cause of re-entry and electrical instability [7,34,35]. Whether MFB falls into this same category remains to be proved, but it certainly is a possibility that must be considered.…”
Section: Discussionmentioning
confidence: 92%
“…Ischemia is the most likely culprit for this inhomogeneity, but the findings of focal myocardial necrosis and/or fibrosis are common in cases of sudden arrhythmic death and are often assumed to be the cause of re-entry and electrical instability [7,34,35]. Whether MFB falls into this same category remains to be proved, but it certainly is a possibility that must be considered.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, while certain authors require that the diagnosis of commotio cordis is used only if structural damage to the sternum, ribs and heart is absent, 4,9 others have applied the diagnosis in the presence of rib fractures, minor pulmonary interstitial hemorrhage and cardiac bruising, the latter attributed to attempted resuscitation. 10,11 Thus, consistency in reporting is lacking. As well, not every case that has been attributed to commotio cordis has had an autopsy examination, occurring in only 75% of cases in one series, 4 and so cardiac contusion has not always been definitively excluded.…”
Section: Discussionmentioning
confidence: 96%
“…The blood alcohol concentration of 0.218% may have played a role in the death given that alcohol is known to sensitize the heart to catecholamines and cause cardiac rhythm disorders. 10,20 Ettinger et al coined the phrase "holiday heart" to describe the development of arrhythmias during episodes of binge drinking. 21 They concluded that cardiac arrhythmias may be induced by heavy alcohol consumption and prolonged alcohol exposure with possible mechanisms including elevated catecholamines, electrolyte disturbances, repolarization abnormalities with prolonged QT interval, and impaired vagal heart rate control.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, toxicological analysis in all the cases is crucial. Ethanol sensitizes the heart to catecholamines action and the subsequent production of arrhythmias . Moreover, the presence of arrhythmogenic drugs, as well as an increase in sympathetic activation usually accompanying an assault, releases catecholamine and may predispose individuals to arrhythmias that contribute to commotio cordis.…”
Section: Discussionmentioning
confidence: 99%